Analysis of Marketing Communication Strategies in Increasing Sales Volume of A.M Production House during Covid-19 Outbreak - Muttaqin, Muhammad Tajul; Fauziyah, Azizah; Yusuf, Ismail; Rachmani, Nizza Nadya (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the marketing communication strategy used by A.M Production House in increasing sales volume during the Covid-19 outbreak. The research used in this case is qualitative experimental research, that is, research that does not use calculations or is termed scientific research that emphasizes the natural character of the data source. The sampling method used was nonprobality sampling method, namely purposive sampling. Samples are taken based on certain predetermined criteria. The data collected in this study consisted of primary data and secondary data. Primary data were obtained by means of directional interviews with A.M Production House owners and direct observation in the form of unstructured observations. Secondary data were obtained from previous journals and sales reports. The results of this study A.M Production House has a marketing communication strategy in increasing sales volume and which has been adjusted to this pandemic. so that sales can take place and experience an increase, and this research indirectly complements the previous research.